Pengaruh Temperatur Sintering pada Konstanta Dielektrik Barium Stronsium Titanat (Ba0,2Sr0,8TiO3) yang dibuat dengan Metode Reaksi Fasa Padat: Alpi Zaidah, Suwarni, Agus Supriyanto, Anif Jamaluddin, Yofentina Iriani - Alpi Zaidah, Alpi Zaidah; Suwarni, Suwarni; Agus Supriyanto, Agus Supriyanto; Anif Jamaluddin, Anif Jamaluddin; Yofentina Iriani, Yofentina Iriani (Jurnal Fisika dan Aplikasinya, 2025)
Ba0.2 Sr0.8 TiO3 samples have been fabricated by solid state reaction. The samples were sintered at temperature 900, 1000, and 11000 C for 2 hours. Characterization of sample using XRD. The analysis exibits that the cubic lattice parameter of BST sintered at 900, 1000, and 11000 C are a = b = c respectively 3.913, 3.910, 3.915 nm. The particle sizes and lattice strains of sampel sintered at 900, 1000, and 11000 C respectively 93 nm, 104 nm, 110 nm and 1,58%, 1,51%, 1,49%. Dielectric constant (K) measurements were performed at the range of frequency 0.01 to 10 kHz where the values are maximum at a minimum frequency. The K values for samples sintered at 900, 1000, and 11000 C at minimum frequency are 1388, 3299 and 3870 respectively.